2013
DOI: 10.1111/gcb.12155
|View full text |Cite
|
Sign up to set email alerts
|

Future carbon dioxide concentration decreases canopy evapotranspiration and soil water depletion by field‐grown maize

Abstract: Maize, in rotation with soybean, forms the largest continuous ecosystem in temperate North America, therefore changes to the biosphere-atmosphere exchange of water vapor and energy of these crops are likely to have an impact on the Midwestern US climate and hydrological cycle. As a C4 crop, maize photosynthesis is already CO2 -saturated at current CO2 concentrations ([CO2 ]) and the primary response of maize to elevated [CO2 ] is decreased stomatal conductance (gs ). If maize photosynthesis is not stimulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 61 publications
7
60
1
Order By: Relevance
“…are consistent with reports for rain-fed maize in the Midwest, US (450-612 mm; Hickman et al, 2010;Djaman et al, 2013;Hussain et al, 2013;Zeri et al, 2013;Hamilton et al, 2015). We found similar total ET for maize and biomass sorghum in non-drought conditions, which may reduce concerns over regional hydrologic effects associated with the introduction of biomass sorghum into Midwest crop rotations .…”
Section: C) Maize Cumulative Et Was Eclipsed By Biomass Sorghum Csupporting
confidence: 91%
See 1 more Smart Citation
“…are consistent with reports for rain-fed maize in the Midwest, US (450-612 mm; Hickman et al, 2010;Djaman et al, 2013;Hussain et al, 2013;Zeri et al, 2013;Hamilton et al, 2015). We found similar total ET for maize and biomass sorghum in non-drought conditions, which may reduce concerns over regional hydrologic effects associated with the introduction of biomass sorghum into Midwest crop rotations .…”
Section: C) Maize Cumulative Et Was Eclipsed By Biomass Sorghum Csupporting
confidence: 91%
“…The residual energy balance (REB) method was selected due to its ability to detect relative differences in ET among plots of limited fetch (Kimball et al, 1994). Numerous previous studies have used the REB method for maize and sorghum agroecosystems (Kimball et al, 1994;Triggs et al, 2004;Hickman et al, 2010;Hussain et al, 2013). Previous studies (Kimball et al, 1994;Triggs et al, 2004;Bernacchi et al, 2007;VanLoocke et al, 2012a) have demonstrated that the REB method is appropriate for plots of relatively small fetch, since the implementation of radiometric temperature in aerodynamic resistance equations reduces fetch requirements compared to other micrometeorological methods (Kimball et al, 1994).…”
Section: Micrometeorologymentioning
confidence: 99%
“…4; Table 1). Other experiments have found only modest changes (\15 %) in evapotranspiration fluxes and soil water content with enhanced [CO 2 ] (e.g., Hussain et al 2013;e.g., Inauen et al 2013;e.g., Stocker et al 1997). Large uncertainties in the effect of enhanced [CO2] on future hydroclimate projections, namely through the modification of stomatal resistance, make characterizing the impact of this mechanism on a global scale simply too difficult to quantify for our purposes herein.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in stomatal opening, and hence leaf conductance to water vapor, can strongly affect root-water uptake and hence the soil water balance (Hungate et al 2002;Gedney et al 2006;Betts et al 2007). Hussain et al (2013) showed that a decrease in leaf conductance of Maize caused a reduction of soil water depletion by 5% -10%. Simple measurements of leaf conductance using a portable porometer could provide a quick assessment of transpiration of a plant.…”
Section: Discussionmentioning
confidence: 99%